SP0007 Dealing with psychological distress to optimise outcomes for arthritis pain. (12th June 2018) - Smeets, R.J.
Abstract : As clinicians we are often confronted with patients who suffer from arthritis pain. As most of us working in the field of arthritis, we are specifically trained to assess and treat medical causes in order to relieve pain. However, in daily practice we experience that many patients will develop chronic pain with huge problems in staying active and experiencing moderate to high levels of disability and lower level of quality of life. In my opinion all clinicians should be able to identify psychosocial factors that contribute to the persistence of arthritis pain associated disability and loss of quality of life. Besides these patient relevant psychosocial factors, I will specifically focus on the important role clinician's beliefs/attitudes regarding pain in better treating and coaching patients with chronic arthritis pain. Participants will learn how to look for these potentially contributing factors, how to diagnose the level of functioning of these patients and how to inform patients about their pain and role of important contributing psychosocial factors. I will discuss the way how you might better prescribe pain medication and other pain relieving treatments and finally how you can help them to stay active despite being in pain, reduce the risk of iatrogenic damage, and what type of treatments exist to address contributing psychosocial factors. Finally, I will specifically elaborate on the Fear Avoidance Model as one of the currently most often used theoretical models to assess patients and on which basis a very successful treatment called graded exposure in vivo has been developed. Disclosure of Interest: None declared